Millennials and the gender wage gap: Do millennial women face a glass ceiling? (2020)
This study aims to measure the gender wage gap among millennial workers in Colombia and determine if there is a marked wage difference between millennial women and men. Further, this study analyzes whether millennial women face a glass ceiling, that is, if there is a larger gender wage gap among workers earning relatively high wages. The study data included a sample of 2,144 millennial workers employed in 11 organizations located in the five main cities of Colombia. Oaxaca–Blinder econometric methods of wage decomposition were used to calculate both raw and adjusted gender wage gaps. The latter results in estimating the gender wage gap while controlling for observable characteristics related to individual, family, and labor. The results show that millennial workers in Colombia face gender inequality in the labor market and that professional millennial women experience a distinct glass ceiling. The adjusted gender wage gap is 9.5 percent, and this gap increases with education level, increasing to nearly 14 percent among college-educated workers. This paper contributes to the literature on workplace discrimination and gender wage inequality for younger workers, and it is original in reviewing the gender pay gap in Colombia using a primary dataset. Most of the work in this area has been done mainly in the developed countries and this research add to the findings which had focused on those nations.